A Multimodal Analysis of English Textbook for Vocational High School: A Study of English For Specific Purposes - Hamidah, Mimi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
As part of English for specific purposes, English books for vocational high schools in Indonesia have been widely studied. Many previous researchers have studied need analysis in English books for Vocational High Schools, while studies related to a multimodal approach are still lacking. Therefore, a study of visual and verbal components in the textbook is conducted in this research. The data is taken from multimodal teaching materials in the English book "Forward: for Vocational High School Grade X" and the textbook user. The data are selected from the images along with the text. Miles and Huberman’s perspective on the qualitative method is used in the study. Besides, A combination of Grammar visual design by Kress and Van Leeuwen and Systemic Functional linguistics by Halliday, as the multimodal framework, identifies elements of multimodal existing in the textbook and investigates whether the textbook images assist students’ understanding of the text. As the result of the study, three patterns of visual elements and ideational functions of verbal elements are revealed in this study. Also, pedagogical benefits are given to the presented visual elements to understand the text. Nevertheless, the analysis of visual images in the textbook and the responses of teacher and student show that the colour and size of visual elements should be improved.